Knowledge of Primiparous Mothers about Newborn Care in RSU Aminah Blitar City - Rachmawati, Dewi; Tahta Karima, Mayya; Miftachul Ulum, Mohamad (Nursing and Health Sciences Journal (NHSJ), 2024)
Primiparous mothers always face difficulties in caring for their babies.The purpose of this study was to determine the knowledge of primiparous mothers about newborn care at RSU Aminah Blitar City. This research design uses quantitative descriptive with a sample size of 33 primiparous mothers who meet the inclusion criteria of 20-35 years old and selected using purposive sampling method. Data collection was carried out on February 18 - March 16, 2024, in the Al-Kautsar Room of RSU Aminah Blitar City. The instrument in this study used a questionnaire sheet with a total of 20 questions that had been tested for validity and reliability with validity test results with rtabel 0.381 and reliability test results 0.732. On the questionnaire sheet, each correct answer is given a value of 1 and the wrong answer is given a value of 0. Data analysis with descriptive analysis is presented in the form of percentages. The percentage results are categorized using a qualitative scale: good with percentage results 76-100%, fair with percentage results 56-75% and less with percentage results <56%. Education, age and occupation are factors that influence the knowledge of primiparous mothers because they increase a person's ability to receive information. It was concluded that 73% of mothers had good knowledge because they had a higher level of education, as well as an increasingly mature age, and had a job, The highest score was 97% (160) respondents answered correctly on statements about how to prevent infection, and the lowest score was 73.7% (73) respondents answered correctly on statements about breastfeeding. It is hoped that the results of this study can be used as a discourse in increasing maternal knowledge about newborn care, especially in primiparous mothers, it is hoped that mothers can be more active in seeking information about everything related to newborn care such as attending parenting programs.